Convergence Proof of Some Generalised Backward Differentiation (GBDF) Methods to Solve the General Second Order Ordinary Differential Equations (ODE). - Suleiman, Mohamed (1984)
Methods for the solution of the general second order ODE are discussed. Stiffness and convergence are also defined. Finally proof of convergence is given for certain cases of the GBDF methods for stiff pro blems.